PERAWATAN FASILITAS KAMAR OLEH ROOM BOY DI HOTEL GRAND ELITE PEKANBARU - Cindy Shenora; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Grand Elite Hotel Pekanbaru is the first luxury international business hotel in the Malay heritage city of Pekanbaru (Riau), Sumatra island from Core Hospitality International which offers customers a unique and extraordinary experience with a very comfortable, affordable and irresistible choice, while "It's the EXTRA THOUGHT that makes all the difference" is Motto. If the guest who stays does not get satisfactory service, or is even disappointed / angry, it is possible that the guest will tell his disappointment to others so that it will reduce the number of guests who will come to stay at the hotel. Therefore, this study aims to find out how to maintain room facilities at the Grand Elite Hotel Pekanbaru and also to find out the obstacles in implementing room facilities maintenance at the Grand Elite Hotel Pekanbaru. This study uses a qualitative descriptive method to analyze problems based on data collection techniques in the form of observation, in-depth interviews, and documentation. Maintenance this hotel room facilities use 3 theories including, daily cleaning, general cleaning and decoration. Based on the results of the research that has been done, for the overall results of the observations and interviews, it can be concluded that the Room Boy Facilities Maintenance at the Grand Elite Hotel Pekanbaru has not been fully maintained by the Room Boy at the hotel. Keywords: Hotel, Treatment, Grand Elite Pekanbaru